A model to assess the impacts of cloud computing use on SME performance: a resource-based view - Hussin, Husnayati; Salleh, Noor Afzan; Suhaimi, Mohd Adam; Md Ali, Asma (American Scientific Publishers, 2018)
Currently, cloud computing services that are available in the market are very appealing to SMEs. This is because these services are not only up-to-date in terms of ICT but more importantly they are affordable to them. However, the adoption of the cloud computing services presents significant challenges to the SMEs. They need to determine the appropriate path in order to ensure their sustainable presence in the cloud computing environment. Additionally, SMEs have to assess whether cloud services can provide value to their business. Past research has focused on cloud computing adoption by SMEs; the post-adoption and impacts of cloud computing was not thoroughly investigated. Using the Resource-Based theory, this paper discusses a conceptual model developed to assess the impact of cloud computing on SME performance, mediated by cloud computing benefits. The role of environmental turbulence is also included in the model which is postulated to moderate the effect of cloud infrastructure capability on cloud computing benefits. The model contributes towards understanding the impacts of cloud computing on SMEs from the lens of Resource-based View, and practically can guide SME managers in planning their cloud migration initiative.